As diferentes utilizações do princípio da precaução e a difícil tomada de decisão - Hubner, Alysson (Pontifícia Universidade Católica de São Paulo, 2018)
This article analyzes the precautionary principle and some of its social implications, as their different uses. From the problems from the project of modernity, we can consider a reformulation of scientific principles to address the problems generated by positivist science. The precautionary principle is to protect the environment through the state when the complete absence of scientific knowledge to generate guarantee to irreversible damage. The article is structured in three parts. The first correlates sustainable development to the precautionary principle. The second part deals with the principle of strong and weak precaution, establishing who holds the power to say what is the precautionary principle as well as the legalization process that it follows. The third part deals with the precautionary principle and democracy, trying to observe how some principles guided by the Ministry of Environment contribute to the observation of this problem. The results point to a fragmentation of the precautionary principle which can not be observed from a uniform perspective, but fragmented, and a correlation between the principles contained in the Ministry of the Environment about the caution regarding its meaning “strong sense” of the term . It is also suggested the principle of percentage in place of the precautionary principle in order to achieve an effective practice.